2021
DOI: 10.1038/s41598-021-82872-3
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of HIV-1 recombinant and subtype B near full-length genome among men who have sex with men in South Korea

Abstract: In Korea, subtype B is the predominant variant of HIV-1, but full genome sequencing and analysis of its viral variants are lacking. We performed near full-length genome (NFLG) sequencing and phylogenetic and recombination analyses of fifty plasma samples from HIV-positive men who have sex with men (MSM) from a Korea HIV/AIDS cohort study. Viral genomes were amplified and the near-full-length sequences were determined using next-generation sequencing (NGS) and Sanger sequencing. We focused on the HIV-1 subtype … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Full genome sequencing can be used to confirm recombinants when viruses typing were unclassified or the results of different gene segments were inconsistent. A number of new HIV recombinants have been reported by near-full-length genome sequencing [32][33][34][35]. In this study, 12 recombinants were confirmed by performing full genome sequencing.…”
Section: Discussionmentioning
confidence: 66%
“…Full genome sequencing can be used to confirm recombinants when viruses typing were unclassified or the results of different gene segments were inconsistent. A number of new HIV recombinants have been reported by near-full-length genome sequencing [32][33][34][35]. In this study, 12 recombinants were confirmed by performing full genome sequencing.…”
Section: Discussionmentioning
confidence: 66%
“…Full genome sequencing can be used to con rm recombinants when viruses typing were unclassi ed or the results of different gene segments were inconsistent. A number of new HIV recombinants have been reported by near-full-length genome sequencing [33][34][35][36]. In this study, 12 recombinants were con rmed by performing full genome sequencing.…”
Section: Discussionmentioning
confidence: 94%
“…Additionally, to date, 118 circulating recombinant forms (CRFs) have also been identified according to the Los Alamos HIV sequence database ( 4 ), and unique recombinant forms (URFs) without evident transmission have also been found ( 5 ). Moreover, complex second- or third-generation CRFs resulting from further recombination of existing CRFs ( 6 , 7 ) and more diversified genotypes of HIV-1 have been observed over time ( 7 9 ). A recent study reported that CRFs and URFs account for 16.7% (including CRF01_AE and CRF02_AG) and 6.1% of HIV-1 infections, respectively ( 10 ).…”
Section: Introductionmentioning
confidence: 99%